2022
DOI: 10.3390/math10234517
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Energy Consumption in a Sustainable Smart Manufacturing Model Considering Superior Service, Flexible Demand, and Partial Outsourcing

Abstract: The waste of energy in the present era is a dangerous signal for the future. All categories of consumers should come forward to moderate energy use and prevent wastage. This study focuses on a controllable energy consumption-based sustainable inventory model incorporating variable production rates, improved service, partial outsourcing planning, defective production, restoring reworkable items, disposing of non-reworkable items, and energy-saving steps. Reducing unusual energy consumption in production systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…For this purpose, FUCA and TOPSIS multicriteria analyses were used, as in the works of Duc [42], who demonstrated that the FUCA method could be used in mechanical processing for multicriteria decision making that did not require data standardization. To select the best scenarios from the simulation and sensitivity analysis, eight decision variables were considered, which competed based on the maximum and minimum optimization criteria according to Bachar et al [26]. These authors used a traditional technique to examine the global optimization of the profit and decision function variables in an energy consumption project of an intelligent manufacturing company, where the demand was considered flexible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, FUCA and TOPSIS multicriteria analyses were used, as in the works of Duc [42], who demonstrated that the FUCA method could be used in mechanical processing for multicriteria decision making that did not require data standardization. To select the best scenarios from the simulation and sensitivity analysis, eight decision variables were considered, which competed based on the maximum and minimum optimization criteria according to Bachar et al [26]. These authors used a traditional technique to examine the global optimization of the profit and decision function variables in an energy consumption project of an intelligent manufacturing company, where the demand was considered flexible.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Use of the multicriteria method for the selection of the best scenarios Selection of the most critical variables to apply a multicriteria decision making TOPSIS and FUCA. [14,[26][27][28] Mathematical models and metaheuristic algorithms…”
Section: Author (S)mentioning
confidence: 99%
“…We refer to [8,[13][14][15][16] for a comprehensive review. There is also some other literature on environmental protection and sustainability from the perspective of energy consumption, transportation hazard, and new technologies, such as Bachar et al [17], Hota et al [18], and Sarkar et al [19]. However, we consider product recovery strategies with remanufacturing.…”
Section: Remanufacturing and Product Recoverymentioning
confidence: 99%
“…They discuss mathematical models involving variables from different sources to maximize profit. Mishra et al (2020) [75] considered the situation characterized by the need to limit carbon emissions; Bachar et al (2022) [76] investigated the use of partial outsourcing to satisfy customer demands; Padiyar et al (2022) [77] considered problems of product deterioration and inflation that introduce uncertainties into inventory management, and considered variables from suppliers, producers, and retailers. Sarkar et al (2022) [78] focused on the use of emerging technology in supply chain management, namely, radio frequency identification (RFID), to optimize warehouse layout.…”
Section: Knowledge Gapsmentioning
confidence: 99%